A method for determining benzo(a)pyrene in air samples collected on glass fiber filters in occupational areas. - Sollenberg, Jan (Scandinavian Journal of Work, Environment & Health, 1976)
Benzo(a)pyrene was analyzed in air samples collected on glass fiber filters in occupational areas. Vacuum sublimation, thin-layer chromatography on acetylated cellulose, and fluorescence scanning of the thin layer plate were performed. The recovery of the method was estimated by an isotope dilution technique using 3H-benzo(a)pyrene. Special equipment was constructed for sublimation. The detection limit for authentic samples was found to be about 10 pmoles per filter.
Keywords: air sample; analysis; benzo(a)pyrene; determination; glass fiber; glass fiber filter; occupational area; polycyclic aromatic hydrocarbon; workroom air